Impurity profiling of methamphetamine synthesized from methyl α‐acetylphenylacetate. Issue 7 (29th March 2022) - Langone, Deanna; Painter, Ben; Nash, Clark; Hulshof, Janneke; Oldenhof, Sander; Johnston, Martin R.; Kirkbride, K. Paul
Abstract: The group of P2P precursors including α ‐phenylacetoacetonitrile (APAAN), α ‐phenylacetoamide (APAA) and methyl α ‐acetylphenylacetate (MAPA) has become increasingly popular in Europe and other parts of the world in the last decade. Previous investigations have reported the use of APAAN in the synthesis of amphetamine and methamphetamine and identified a range of characteristic impurities. This research has expanded upon the current literature by investigating the use of MAPA in the synthesis of methamphetamine. In this study methamphetamine was synthesized via three common clandestine methods: the Leuckart synthesis and two reductive amination methods. We report the identification of seven impurities, four of which are methyl ester equivalents of impurities previously reported for the detection of APAAN. These are methyl 2‐phenylbut‐2‐enoate, methyl 2‐phenyl‐3‐hydroxybutanoate, methyl 3‐(methylamino)‐2‐phenylbut‐2‐enoate and methyl 3‐(methylamino)‐2‐phenylbutanoate. The other impurities identified are ethyl ester compounds formed via transesterification of the methyl ester due to the reaction solvent. This susceptibility for transesterification suggests that identification of the pre‐precursor used may not always be straightforward and may be dependent on the reaction conditions employed. Of the impurities reported, methyl 3‐(methylamino)‐2‐phenylbutanoate was deemed to be a potentially reliable impurity for detection of the use of MAPA; however, it is expected that lower levels of characteristic impurities may be detected in methamphetamine synthesized from MAPA than that from APAAN. Abstract : Impurity profiling was carried out on methamphetamine synthesized from the pre‐precursor methyl α ‐acetylphenylacetate (MAPA). Three methamphetamine synthesis reactions were tested, and seven characteristic impurities were identified and characterized.